2017
DOI: 10.1002/jbio.201600244
|View full text |Cite
|
Sign up to set email alerts
|

Low‐level light emitting diode (LED) therapy suppresses inflammasome‐mediated brain damage in experimental ischemic stroke

Abstract: Use of photostimulation including low-level light emitting diode (LED) therapy has broadened greatly in recent years because it is compact, portable, and easy to use. Here, the effects of photostimulation by LED (610 nm) therapy on ischemic brain damage was investigated in mice in which treatment started after a stroke in a clinically relevant setting. The mice underwent LED therapy (20 min) twice a day for 3 days, commencing at 4 hours post-ischemia. LED therapy group generated a significantly smaller infarct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 64 publications
3
44
0
Order By: Relevance
“…Interestingly, PBM therapy prevented stress-induced alteration of the BAX/Bcl-2 ratio and avoided an increase in caspases activity most likely through the preservation of MMP and a reduction of cytochrome c leakage into the cytoplasm. Our results are consistent with other studies showing anti-apoptotic effects of red/NIR PBM therapy via inhibition of the intrinsic mitochondrial apoptosis pathway in animal models of aging (Salehpour, et al, 2017), AD (Lu, et al, 2017), stroke (Lee, et al, 2017), and TBI (Xuan et al, 2014). Although our findings suggest that the anti-apoptotic activity may also contribute to the antidepressant-like effects of PBM therapy, the ability of NIR light to inhibit stress-mediated cell apoptosis needs further investigation.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Interestingly, PBM therapy prevented stress-induced alteration of the BAX/Bcl-2 ratio and avoided an increase in caspases activity most likely through the preservation of MMP and a reduction of cytochrome c leakage into the cytoplasm. Our results are consistent with other studies showing anti-apoptotic effects of red/NIR PBM therapy via inhibition of the intrinsic mitochondrial apoptosis pathway in animal models of aging (Salehpour, et al, 2017), AD (Lu, et al, 2017), stroke (Lee, et al, 2017), and TBI (Xuan et al, 2014). Although our findings suggest that the anti-apoptotic activity may also contribute to the antidepressant-like effects of PBM therapy, the ability of NIR light to inhibit stress-mediated cell apoptosis needs further investigation.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, in our study, PBM suppressed restraint stress-induced activation of microglia and secretion of pro-inflammatory signaling mediators, namely NF-kB, JNK, and p38, in the HIP and PFC areas. Pre-clinical investigations also demonstrated that transcranial PBM exhibited strong anti-neuroinflammatory actions via inhibition of NF-kB signaling pathways in stroke models (Lee et al, 2017; Lee et al, 2016). Furthermore, in agreement with our results, these studies reported that PBM therapy diminished neuroinflammation in the ischemic cortex of mice via down-regulation of the expression of JNK and p38 (Lee, et al, 2017; Lee, et al, 2016).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Mice received treatment using a skin-adhesive LED light source (Color Seven Co., Seoul, Korea) as pre-viously reported [18]. For LED-T, a device with a peak wavelength of 610 nm (orange color) was placed on the skin at 2 concurrent locations on the head (the right midpoint of the parietal bone and the posterior midline of the seventh cervical vertebra) using double-sided tape ( Figure 1B).…”
Section: Low-level Light Emitting Diode Therapymentioning
confidence: 99%
“…The beneficial effects of LLLT on new synaptic connections have been shown to contribute to neural repair processes during the reorganization of brain tissues [14,16]. We recently reported that lightemitting diode therapy (LED-T) exerts neuroprotective effects against acute brain injury after focal cerebral ischemia [17,18]. Pre-conditioning or immediate treatment with LED-T after an ischemic insult can be effective against acute brain injury by aiding in anti-inflammation, blood-brain barrier protection, and neuroprotection [17,18].…”
Section: Introductionmentioning
confidence: 99%